Practical guide to the management of acute pancreatitis. Issue 3 (2nd March 2019) - Goodchild, George; Chouhan, Manil; Johnson, Gavin J
Abstract : Acute pancreatitis (AP) is characterised by inflammation of the exocrine pancreas and is associated with acinar cell injury and both a local and systemic inflammatory response. AP may range in severity from self-limiting, characterised by mild pancreatic oedema, to severe systemic inflammation with pancreatic necrosis, organ failure and death. Several international guidelines have been developed including those from the joint International Association of Pancreatology and American Pancreatic Association, American College of Gastroenterology and British Society of Gastroenterology. Here we discuss current diagnostic and management challenges and address the common dilemmas in AP.